PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE LEARNING TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN BAHASA INDONESIA SISWA KELAS V SD NEGERI 27 TONASA KAB. PANGKEP: Penelitian tindakan kelas - Putri Yasmin; Muhammad Akhir; Maria Ulviani (STKIP Subang, 2025)
This research is a classroom action research aimed at determining the improvement of students' learning outcomes through the implementation of the cooperative learning model of the Learning Together type. Based on the data analysis and discussion, it can be concluded that the application of the cooperative learning model of the Learning Together type in Indonesian language lessons can improve students' learning outcomes. This can be seen and proven from the average scores in Cycle I and Cycle II. The average score in Cycle I was 57.2%, while the average score in Cycle II increased to 85%. Therefore, the analysis of students' learning outcomes proves that the implementation of the cooperative learning model of the Learning Together type can improve the learning outcomes of fifth-grade students at SD Negeri 27 Tonasa, Pangkep Regency, in Indonesian language lessons.